2023
DOI: 10.3389/fneur.2023.1148152
|View full text |Cite
|
Sign up to set email alerts
|

Absence of susceptibility vessel sign and hyperdense vessel sign in patients with cancer-related stroke

Abstract: Background and aimIdentification of paraneoplastic hypercoagulability in stroke patients helps to guide investigations and prevent stroke recurrence. A previous study demonstrated an association between the absence of the susceptibility vessel sign (SVS) on brain MRI and active cancer in patients treated with mechanical thrombectomy. The present study aimed to confirm this finding and assess an association between the absence of the hyperdense vessel sign (HVS) on head CT and active cancer in all stroke patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[40][41][42] As mentioned earlier, retrieved thrombi from cases with stroke caused by cancerrelated hypercoagulability exhibit minimal erythrocyte components, as evidenced by Jung et al's study, 26) where all 19 cases of cancer-related cryptogenic stroke showed absence of SVS. Beyeler et al 43) also showed a significant association between absence of SVS and active cancer (aOR, 3.14; 95% CI, 1.45-6.80) from a large thrombectomy cohort analysis including a total of 2256 cases. Additionally, platelet-rich thrombi have been reported to show isoattenuation (Hounsfield Unit value <50) on non-contrast CT. 44) The absence of HVS/SVS findings might, thus, suggest the presence of stroke caused by cancer-related hypercoagulability in patients with cancer-associated stroke.…”
Section: Imaging and Serum Biomarkers For Preoperative Diagnosis Of S...mentioning
confidence: 89%
“…[40][41][42] As mentioned earlier, retrieved thrombi from cases with stroke caused by cancerrelated hypercoagulability exhibit minimal erythrocyte components, as evidenced by Jung et al's study, 26) where all 19 cases of cancer-related cryptogenic stroke showed absence of SVS. Beyeler et al 43) also showed a significant association between absence of SVS and active cancer (aOR, 3.14; 95% CI, 1.45-6.80) from a large thrombectomy cohort analysis including a total of 2256 cases. Additionally, platelet-rich thrombi have been reported to show isoattenuation (Hounsfield Unit value <50) on non-contrast CT. 44) The absence of HVS/SVS findings might, thus, suggest the presence of stroke caused by cancer-related hypercoagulability in patients with cancer-associated stroke.…”
Section: Imaging and Serum Biomarkers For Preoperative Diagnosis Of S...mentioning
confidence: 89%
“…Histological thrombus composition in LVO may represent an interesting research question, as it is an important feature that may help to specify stroke pathogenesis, differentiating between cardioembolic and atherothrombotic stroke causes. Further clinical and radiological factors predicting stroke etiology might support histological findings, i.e., considering the systematic assessment of hyperdense vessel signs in native computed tomography and/or susceptibility vessel signs in susceptibility-weighted imaging on brain magnetic resonance imaging [39]. Our study showed the presence of FCs in approximately one-third of the retrieved clots, but the identification of the clot that presumably comes from the atheromatous plaque rupture tended to disagree with the clinical diagnosis, even if the difference between FC and NFC groups did not reach the statistical significance.…”
Section: Discussionmentioning
confidence: 99%